Rapid initiation of antiretroviral therapy in Turkey: a modeling study - Yaylali, Emine; Erdogan, Zikriye Melisa; Calisir, Fethi; Pullukcu, Husnu; Yildirim, Figen; Inan, Asuman; Aydin, Ozlem Altuntas; Tekin, Suda; Sonmezer, Meliha Cagla; Sahin, Toros; Ozcagli, Tahsin Gokcem; Ozelgun, Berna (Frontiers in Public Health, 2024)
Background To effectively control the HIV epidemic and meet global targets, policymakers recommend the rapid initiation of antiretroviral therapy (ART). Our study aims to investigate the effect of rapid ART programs on individuals diagnosed with HIV, considering varying coverage and initiation days after diagnosis, and compare it to standard-of-care ART treatment in Turkey. Methods We used a dynamic compartmental model to simulate the dynamics of HIV infection in Turkey. Rapid treatment, defined as initiation of ART within 7 days of diagnosis, was contrasted with standard-of-care treatment, which starts within 30 days of diagnosis. This study considered three coverage levels (10%, 50%, and 90%) and two rapid periods (7 and 14 days after diagnosis), comparing them to standard-of-care treatment in evaluating the number of HIV infections between 2020 and 2030. Results Annual HIV incidence and prevalence for a 10-year period were obtained from model projections. In the absence of a rapid ART program, the model projected approximately 444,000 new HIV cases while the number of cases were reduced to 345,000 (22% reduction) with 90% of diagnosed cases included in the rapid ART program. Similarly, 10% and 50% rapid ART coverage has resulted in 3% and 13% reduction in HIV prevalence over a 10-year period. Conclusion Rapid ART demonstrates the potential to mitigate the increasing HIV incidence in Turkey by reducing the number of infections. The benefit of the rapid ART program could be substantial when the coverage of the program reaches above a certain percentage of diagnosed population.